Setting a universal standard: Should we benchmark quality outcomes for pediatric anesthesia care?. Issue 8 (5th May 2022) - Olbrecht, Vanessa A.; Uffman, Joshua C.; Morse, Rustin B.; Engelhardt, Thomas; Tobias, Joseph D.
Abstract: Anesthesiology is a medical specialty well known for its work in patient safety, allowing the field to show a dramatic decrease in perioperative morbidity and mortality in both adults and children since the 1950s. Currently, anesthesia‐related mortality is close to zero in healthy children, with deaths occurring primarily in children ASA physical status ≥4. Survival during anesthesia today represents the expectation and standard of care, rather than a marker of quality. Several programs and organizations have created measures to assess safety in pediatric anesthesia—yet none are universally accepted as safety metrics or bundled to evaluate specific aspects of care. In addition, collection of this nonstandardized data in individual centers requires a significant investment of resources and personnel limiting access to only large, "resource‐rich" institutions. In this perspective paper, we provide an overview of the efforts made to enhance quality of care across medical specialties with a specific emphasis on pediatric anesthesiology. We discuss the need for standardization of metrics to establish targets and benchmarks for the delivery of high‐quality care to children and adolescents mainly in North America. The time has come to move beyond mortality and establish universally accepted minimum outcome standards in pediatric anesthesia. We believe this will ultimately improve confidence in the quality of pediatric anesthesia care offered to children, no matter where they are receiving that care.